Magnetic field-assisted assembly of iron oxide mesocrystals: a matter of nanoparticle shape and magnetic anisotropy - Brunner, Julian J.; Krumova, Marina; Cölfen, Helmut; Sturm (née Rosseeva), Elena V. (Beilstein Journal of Nanotechnology, 2019)
This letter describes the formation and detailed characterization of iron oxide mesocrystals produced by the directed assembly of superparamagnetic iron oxide-truncated nanocubes using the slow evaporation of the solvent within an externally applied homogeneous magnetic field. Anisotropic mesocrystals with an elongation along the direction of the magnetic field can be produced. The structure of the directed mesocrystals is compared to self-assembled mesocrystalline films, which are formed without the influence of a magnetic field. The remarkable structural difference of mesocrystals produced within the external magnetic field from those self-assembled without field indicates that the specific nanoparticle ordering within the superstructure is driven by competing of two types of anisotropic interactions caused by particle shape (i.e., faceting) and orientation of the magnetic moment (i.e., easy axes: <111>magnetite). Hence, these findings provide a fundamental understanding of formation mechanisms and structuring of mesocrystals built up from superparamagnetic nanoparticles and how a magnetic field can be used to design anisotropic mesocrystals with different structures.
Keywords: directed assembly; magnetite; mesocrystal; nanoparticle; transmission electron microscopy